(3GdQSGdI GdgGOjI HGdCOdI GdHGOjI aj HjGf CMcGe Cgd GdQOIs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdMeO Edi eRjO EMSGfg SdekG hdeG fLe fGLe GdaQbI GdedYhfI GdeQJOI GdeaJhfI GdeSeGg HGdeWQajI s
(3BNQgG (B:s
(3heG CQOj Gf CNGdace Edi eG CfgG ce Yfg Ef CQjO EdG GdCUdGM eG ESJWYJ hGdMeO ddg JeJ GdQSGdI s
(3cJHJ ahGJMgG HGdSecs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds